2021
DOI: 10.1016/j.neo.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of immune checkpoint proteins in histological subtypes of lung adenocarcinoma

Abstract: The most prevalent histological type of non-small cell lung cancer (NSCLC) is adenocarcinoma. The WHO classifies this tumor into subtypes according to the predominant growth pattern such as lepidic, acinar, papillary, solid or micropapillary, each harboring specific molecular features. NSCLC adenocarcinoma heterogeneity is discussed to be a reason for therapy failure using targeted therapy or immune checkpoint inhibitors. For successful therapy of immune checkpoint inhibitors the expression and distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Next, we showed that CD155-positivity was significantly associated with aggressive cancer behavior such as pleural/vascular invasion and was a significant factor to predict a poor prognosis. Previous clinical studies in NSCLC also showed that CD155-positivity was correlated with a poor prognosis ( 14 , 16 21 ). However, characteristics of patients included in previous studies were too heterogenous to draw a definitive conclusion.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Next, we showed that CD155-positivity was significantly associated with aggressive cancer behavior such as pleural/vascular invasion and was a significant factor to predict a poor prognosis. Previous clinical studies in NSCLC also showed that CD155-positivity was correlated with a poor prognosis ( 14 , 16 21 ). However, characteristics of patients included in previous studies were too heterogenous to draw a definitive conclusion.…”
Section: Discussionmentioning
confidence: 75%
“…The present study revealed the detailed CD155 expression in lung adenocarcinoma. As the TIGIT/CD155 axis has emerged as a novel therapeutic target in a variety of malignant tumors, several studies on the CD155 expression in NSCLC including lung adenocarcinoma have been reported ( 14 21 ). However, no study has previously reported detailed distribution of tumoral CD155 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their durable response, ICI monotherapy has a response rate of at most 20%, leading to the development of combinations of ICIs. Basic research reported good prospects for combination therapy with multiple ICIs 3 , 4 , which has also been proven in clinical studies 5 8 . In the phase II CITYSCAPE trial, anti-T cell immunoglobulin and immunoreceptor tyrosine-based inhibitory motif (ITIM) domain (TIGIT) antibody tiragolumab combined with the PD-L1 inhibitor atezolizumab significantly improved the overall response rate compared to anti-PD-L1 monotherapy (37% vs. 21%) (37% vs. 21%) 9 .…”
Section: Introductionmentioning
confidence: 93%
“…Florian Länger (Hannover) gab einen sehr umfassenden Überblick zu interstitiellen Lungenerkrankungen im Säuglings- und Kindesalter, der sicher einen längeren Slot verdient hätte [ 5 ]. Ralf Marienfeld (Ulm) trug die Ergebnisse zur räumlichen Verteilung der Immuncheckpoint-Proteine in unterschiedlichen morphologischen Subtypen von Adenokarzinomen der Lunge vor [ 6 ]. Philip Bischoff (Berlin) berichtete zur Charakterisierung des Tumormikromilieus in Adenokarzinomen der Lunge mittels Einzelzell-RNA-Sequenzierung.…”
Section: Virtuelle Pathologietage 2021unclassified